On the Mechanism of the [3+2]-Cycloaddition of Phenylnitroso Oxide to trans-Stilbene - Khursan, Vitaly S.; Chainikova, Ekaterina M.; Khursan, Sergey L.; Safiullin, Rustam L. (Letters in Organic Chemistry, 2019)
The non-photolytic method for generation of arylnitroso oxides based on the reduction of nitrosobenzene by triphenylphosphine was used to study the products of the reaction of transphenylnitroso oxide with trans-stilbene. N,α-Diphenylnitrone and benzaldehyde were found to be the main stable products of the reaction, the first stage of which was [3+2]-cycloaddition to form the metastable 1,2,3-dioxazolidine intermediate. The obtained products were in agreement with our previous theoretical predictions.
Keywords: [3+2]-cycloadditon to stilbene